CONSTITUTIONAL ISSUES RAISED BY THE RATIFICATION OF THE ICC STATUTE - Hakobyan, Davit (State and Law, 2022)
This article presents in general the main principles of the exercise of the jurisdiction of the International Criminal Court (hereinafter referred to as the ICC or the Court), the existing concerns regarding the ratification of the Court and well-founded arguments against them. The article based on the practice discusses under which circumstances the International Criminal Court can deal with the 1st Nagorno Karabakh war, and what are the main priorities for the Prosecutor’s Office. Plausible options for ratification of the ICC Statute are also discussed, in particular, the possibility of revising the constitutionality of the obligations stipulated in the ICC Statute before the Constitutional Court of the Republic of Armenia and/or the need to amend the Constitution for the purpose of ratifying the ICC Statute. The article also discusses the ways the constitutional courts can overcome constitutional challenges that they usually face while adjudicating over the constitutionality of the ICC statute.
Keywords: International Criminal Court; ICC Statute Ratification; ICC jurisdiction; ICC Triggering Mechanism; Review of the Decision of the Constitutional Court; Constitutional Revision; Situations under the ICC